Modeling and quantifying surface water resource potential in Awash Bello watershed, Upper Awash River Basin, Ethiopia, using SWAT model - Tilahun, Rahel Abebe; Worku, Hailu; Mengistu, Aramde Fetene (Frontiers in Water, 2026)
Rising global water demand, combined with climate change, population growth, industrial development, and land use change, highlights the need for quantifying water resources for long-term planning. This study specifically focuses on quantifying surface water resource potential with its seasonal variation in the Awash Bello watershed. The surface water resource potential was quantified using ArcGIS10.4.1, Arc SWAT 2012, and SUFI-2 algorithms in Soil and Water Assessment Tool - Calibration and Uncertainty Program (SWAT-CUP). The meteorological data (1990–2022) and stream flow data (1993–2016) were utilized in the data analysis. The watershed was established to delineate 35 sub-catchments and 236 Hydrological Response Units. Calibration and validation for the SWAT model and sensitivity analysis were also performed. The results of the hydrological model for Awash Bello watershed, covering 4,490 km2, estimate approximately 949.43 million cubic meters of annual surface runoff, with a runoff depth of 211.46 mm and total rainfall of 1,074.78 mm. The “Kiremt” season (June, July, August, and September) contributes to 71.21% of annual rainfall, while the “Bega” season (October, November, December, and January) accounts for only 5.58%. In contrast, the “Belg” season, which comprises February, March, April, and May, contributes to 23.21% of the annual rainfall, and it is greater than “Bega.” These results thus highlight the importance of surface water resource management in conserving the runoff and enhancing groundwater recharge toward sustainable water resource management, particularly during periods of dry season and periods of low water balance, ensuring water scarcity is mitigated.